2009
DOI: 10.1186/1758-5996-1-17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carnitine and herbal mixture extract on obesity induced by high fat diet in rats

Abstract: Background: Obesity-associated type 2 diabetes is rapidly increasing throughout the world. It is generally recognized that natural products with a long history of safety can modulate obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
100
2
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(122 citation statements)
references
References 81 publications
18
100
2
2
Order By: Relevance
“…Similar observations were reported in several studies (He et al, 2008;Amin and Nagy, 2009;Koya-Miyata et al, 2009;Lee et al, 2009;Bhalodia et al, 2010;Rachh et al, 2010). Administration of Coenzyme Q10 for last month inhibited the percentage change of body weight in rats treated with high cholesterol diet and con oil.…”
Section: Discussionsupporting
confidence: 77%
“…Similar observations were reported in several studies (He et al, 2008;Amin and Nagy, 2009;Koya-Miyata et al, 2009;Lee et al, 2009;Bhalodia et al, 2010;Rachh et al, 2010). Administration of Coenzyme Q10 for last month inhibited the percentage change of body weight in rats treated with high cholesterol diet and con oil.…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, there was a statistically significant increase (P<0.01) in the plasma glucose level in both the FD group and the FD+TQ group as compared with their control groups respective. The reason for this may be that the high fat diet induced hyperglycemia, hyperinsulinemia and insulin resistance [9] . However, the short experimental period of this study may not have been long enough to observe hyperinsulinemia and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, however, the numerical increases in body weight were found to be statistically insignificant in the FD group compared to the control group at the end of the 6 th week. Several studies reported that body weights in high fat diet groups were heavier than standard diet groups during 6-12 week periods [9,10] . The reason for this result may be due to the short experimental period of this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations